MODERATING EFFECT OF BUSINESS RISK ON THE AUDIT FEE MODEL AMONG SMALL AUDIT FIRMS: CASE OF WESTERN REGION, KENYA - Isaac Naibei, Kiprotich; Oima, David; Ojera, Patrick (European Scientific Journal, ESJ, 2014)
Auditing remains a fundamental tool of financial managementoversight. Despite of auditing ability to enhance confidence and reliability ofthe financial statements, there has been increasing criticisms addressed to theaudit profession in the recent past especially after the failure of severalinternational and local companies which occasioned doubt on the oversightrole of audit due to its overreliance on financial statements at the expense ofbusiness risks. Consequently, auditors have been compelled to reengineertheir audit approaches to be more responsive to business risks. The purposeof this study was to evaluate the moderating impact of business risks on therelationship between audit fees and its determinants among audit firms inWestern Region, Kenya using cross-sectional survey research design with atarget population of 48 Audit firms. Saturated sampling technique was usedin which data was collected using self administered questionnaires. Thestudy revealed existence of significant moderating effect of business risks onthe both audit duration and size of the audit firm – audit fee relationship. Thestudy concludes that client‘s size, complexity as determined by number ofsubsidiaries and branches and audit firm size are the major determinants ofaudit fee and that their effect can further be enhanced by business risks, themoderator variable. The study provides rationale for BRA and its findingsprovides direction for response to business risks among audit practitioners aswell as enriching the literature of audit risk and fee model with evidencesfrom emerging economies.